2009
DOI: 10.1038/nsmb.1703
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of potassium-channel selectivity revealed by Na+ and Li+ binding sites within the KcsA pore

Abstract: Potassium channels allow K+ ions to easily diffuse through their pores while effectively preventing smaller Na+ ions from permeation. The ability to discriminate between these two similar and abundant ions is vital for these proteins to control electrical and chemical activity in all organisms. This selection process occurs at the narrow selectivity filter that contains structurally identified K+ binding-sites. Selectivity is thought to arise because smaller ions such as Na+ do not bind to these K+ sites in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
200
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(225 citation statements)
references
References 58 publications
22
200
0
1
Order By: Relevance
“…[22][23][24]. These studies showed that the cage-of-oxygen sites provide selective binding for K þ over Na þ , by up to 5 kcal∕mol, reinforcing the view that K þ channels exclude Na þ ions due to differing thermodynamic stabilities in the crystallographic sites.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…[22][23][24]. These studies showed that the cage-of-oxygen sites provide selective binding for K þ over Na þ , by up to 5 kcal∕mol, reinforcing the view that K þ channels exclude Na þ ions due to differing thermodynamic stabilities in the crystallographic sites.…”
mentioning
confidence: 68%
“…Perhaps higher barriers for Na þ may arise due to the different multi-ion configurations for Na þ or K þ -Na þ mixtures. We previously showed, for the case of ion entry from the intracellular side, that the presence of Na þ , with different (by ∼1 Å) binding site locations, disrupts the optimized knock-on conduction mechanism of KcsA, leading to large permeation barriers (24). We suggest that such an elevated barrier for Na þ may also exist for entry from the external solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the availability of a number of high-resolution structures of K þ channels has greatly aided our understanding of the molecular details of ion binding in this highly conserved structure (3)(4)(5)(6), the underlying mechanism of K þ selectivity remains elusive (7)(8)(9)(10)(11)(12). The structural studies of K þ channels seem to favor the classical snug-fit model to account for K þ over Na þ selectivity (13,14), while computational studies on K þ channel selectivity invoke a number of different concepts in explaining K þ selectivity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%